High Voltage Distribution System For Loss Reduction - Che Wan Osman, Che Wan Mohd Nor Sofian (Universiti Sains Malaysia, 2005)
Electricity is modern society’s most convenient and useful form of energy. Without it, the present social infrastructure would not all be feasible. The increasing per capita consumption of electricity throughout the world reflects a growing standard of living of the people. The optimum utilization of this form of energy can only be ensured by effective distribution systems. A distribution system is the one from which the power is distributed to various consumers through feeders, distributors and service mains. Feeders are conductors of large current carrying capacity carrying the current in bulk to the feeding points. Distributors are conductors from which the current is tapped off the supply to the consumer premises. Because of lower voltage, and hence higher current, the I 2 R loss in the distribution system is significantly high compared to that of a high-voltage transmission system. The pressure of improving the overall efficiency of power distribution has forced the power utilities to reduce the loss, especially at the distribution level. The I2 R loss in a distribution system can be reduced by network reconfiguration. The reconfiguration changes the path of power flow from source to the loads. A program has been developed based on MATLAB program to do the analysis in this project.The perfomance of the proposed method was investigated on distribution system consisting of 33 buses and it was found that a significant loss saving can be achieved by using a of High Voltage Distribution System.